2010
DOI: 10.3748/wjg.v16.i44.5598
|View full text |Cite
|
Sign up to set email alerts
|

Left-sided appendicitis: Review of 95 published cases and a case report

Abstract: The diagnosis of left lower quadrant pain is based on well-established clinical symptoms, physical examination and physician's experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
124
0
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(140 citation statements)
references
References 41 publications
0
124
0
11
Order By: Relevance
“…Furthermore, only seven presented with left upper quadrant pain, but none of them were reported to have renal agenesis. [9] Another case was reported in 2015 of 6-year-old boy with gangrenous appendicitis in the epigastric area and underwent surgery. In contrast to their case, we found acute gangrenous appendicitis in an adult, extending laterally to the left upper quadrant and treated conservatively.…”
Section: Discussion:-mentioning
confidence: 99%
“…Furthermore, only seven presented with left upper quadrant pain, but none of them were reported to have renal agenesis. [9] Another case was reported in 2015 of 6-year-old boy with gangrenous appendicitis in the epigastric area and underwent surgery. In contrast to their case, we found acute gangrenous appendicitis in an adult, extending laterally to the left upper quadrant and treated conservatively.…”
Section: Discussion:-mentioning
confidence: 99%
“…Abnormalities including intestinal malrotation, mobile cecum and SIT may result in left-sided appendicitis (1,6,7). In situs inversus totalis, all intrathoracic and abdominal organs are localized completely in the opposite side.…”
Section: To the Editormentioning
confidence: 99%
“…Collins et al (7) reported the prevalence of left-sided appendicitis to be 0.04% and the prevelance of association of SIT and left-sided appendicitis to be 0.016%. Less than 100 cases have been reported in the literature (6).…”
Section: To the Editormentioning
confidence: 99%
“…The diagnosis is based on well-established clinical symptoms and basic radiological examination (1). Epididymitis is the most common cause of testicular pain, and usually shows acute onset (2).…”
Section: Introductionmentioning
confidence: 99%